Phytogenic fabrication of ZnO and gold decorated ZnO nanoparticles for photocatalytic degradation of Rhodamine B. Issue 1 (February 2021) - Ahmad, Munir; Rehman, Wajid; Khan, Mohammad Mansoob; Qureshi, Muhammad Tauseef; Gul, Anadil; Haq, Sirajul; Ullah, Rizwan; Rab, Abdur; Menaa, Farid
Graphical abstract: Highlights: Green synthesis of Au/ZnO nanoparticles by using Carya illinoinensis leaf extract. Photocatalytic degradation of Rhodamine B dye by using ZnO and Au/ZnO nanoparticles was studied. Gold modified Au/ZnO nanoparticle exhibited higher degradation efficiency than bare ZnO. Checked the influence of different parameters (pH, dose of catalyst, dye concentration) on degradation activity. The degradation of Rhodamine B dye followed pseudo first order model. Abstract: Pure Zinc Oxide (ZnO) nanoparticles (NPs) and gold (Au) decorated (Au-ZnO) hetero-nanostructures were synthesized using green-synthesis method employing pecan nuts ( Carya illinoinensis ) leaves extract as reducing agent. The structural and optical properties studied by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), High-resolution transmission electron microscopy (HRTEM) and UV–vis spectrophotometer (UV–vis). Structural modification with the introduction of Au in ZnO have been confirmed by the XRD and TEM results. UV data confirmed the decrease in Au-ZnO energy band-gap Eg value, which validates the formation of hetero-structure. The modulation of energy band-gap causes visible light absorption and hence enhances the photodegradation activity of Au-ZnO. Photocatalytic activity was carried-out by degradation of RhB dye under UV light irradiation in aqueous solution. The maximum degradation of 95 % was obtained during the time of 180 min for the basic pH of the dye. The Enhanced degradation in Au-ZnO as compared with bare ZnO NPs, was attributed to Au, which controls the amount of electron and suppress electron-hole ratio at ZnO surface. In the recycling study of the Au-ZnO Photocatalyst, the hetero-structure showed good stability up to five cycles.